Examining Incidents of Sexual Misconduct Reported to Title IX Coordinators: Results from New York’s Institutions of Higher Education - Claxton, Taylor (2021)
A paucity of studies has examined incidents of sexual misconduct reported to Title IX coordinators at institutions of higher education (IHEs) or examined differences across types of IHEs. We used 2018 data from incidents of sexual misconduct (N = 3,829) reported to Title IX coordinators at IHEs in New York (N = 209) to examine the context, processes, and outcomes of reported incidents. Findings show that most incidents reported to Title IX coordinators did not prompt the IHE’s conduct process; “other” disciplinary sanctions were the favored response for responsible students, while suspensions and/or expulsions were rarely used. Further data collection and analysis is needed to understand victim and IHE decision-making regarding reported incidents of sexual misconduct and specific processes at community colleges and independent IHEs